PENGARUH PENDEKATAN KONSTRUKTIVISME TERHADAP HASIL BELAJAR PESERTA DIDIK SDN 9 SIANTAN - Nurasyiafitriani, Nurasyiafitriani; Utami, Sri; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstactThe purpose of this study was to analyze how much influence the constructivism approach on learning outcomes of students in science learning class IV SDN 9 Siantan. The method used is an experimental method. The form of the experimental research used was a quasi-experimental design with nonequivalent control group design. The sample in this study were all fourth grade students ofÂ  SDN 9 Siantan totaling 40 people. The average results of the post-test control class were 73 while the average results of the post-test experimental class were 80.5. Based on the analysis using t-test obtained t_count = 3.28 for dk = 38 and Î± = 5% is obtained t table = 1.686, which means t_count (3.28)> t table (1.686), then Ha is accepted. So it can be concluded that there is a significant influence on the use of the constructivism approach to the learning outcomes of students in the science learning class IV SDN 9 Siantan.Â Keywords: Constructivism Approach, Learning Outcomes, Science Learning